II. Net Accumulation of Snow by Stake Measurements in Mizuho Plateau, East Antarctica, 1968-1971 - アゲタ, ユタカ; ワタナベ, オキツグ; AGETA, Yutaka; WATANABE, Okitsugu (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper